Intervención urbano arquitectónica del espacio público en la parroquia de Quimiag, cantón Riobamba. - Barragán Granizo, Hernán Danilo (2022)
This research work seeks as its main objective to generate an urban-architectural proposal aimed at improving public space and facilities in the town center of Quimiag parish. Through an exploratory and documentary research, the diagnosis is carried out at the parish and urban level to later generate an intervention proposal aimed at meeting the relevant needs such as the integration of new recreation spaces, urban growth areas, landscape interventions and other facilities that will be focused on the territorial role of the parish. The need for the creation of new basic infrastructure, public space and architectural breaks is imperative. This also takes a look at the horizon when proposing strategies that enhance the productive and tourist role on a global scale taking benefits of its tourist and productive advantage. It seeks to create a roadmap for the structuring of public policies, alliances and agreements that must be put to the consideration of the community. It starts from a territorial scale until it reaches the architectural object with the intention of creating new circuits and pauses. It seeks to create sustainable and cyclical communities that can become self-sufficient at different levels and variables. The proposal for urban regeneration of the town center is made and architectural urban intervention strategies are proposed for the improvement and repowering of the current public space that turns out to be deficient.